2007
DOI: 10.1364/ao.46.007007
|View full text |Cite
|
Sign up to set email alerts
|

Theory and practice of ubiquitous quantitative chemical analysis using conventional computer optical disk drives

Abstract: We demonstrate a new attractive approach for ubiquitous quantitative chemical or biological sensing when analog signals are acquired from conventional optical disk drives, and these signals are used for quantitative detection of optical changes of sensing films deposited on conventional CD and DVD optical disks. Our developed analytical model of the operation of this Lab-on-DVD system describes the optical response of sensing films deposited onto the read surface of optical disks by taking into account the pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…The error bars reflect one standard deviation from the measurements at these three radial positions. The error bars associated with 650 nm optical disk drive response were ∼1.5-2 times less than from the interferometric profilometer measurements due to the averaging ability of the Lab-on-Disk readout while scanning the sensing films [9,10]. This experiment demonstrated that the film thickness information can be obtained from an optical disk drive-based absorbance measurement of a reference methylene blue reagent in the sensing film at 650 nm.…”
Section: Determination Of Sensing Films Thickness From Optical Disk Dmentioning
confidence: 83%
See 2 more Smart Citations
“…The error bars reflect one standard deviation from the measurements at these three radial positions. The error bars associated with 650 nm optical disk drive response were ∼1.5-2 times less than from the interferometric profilometer measurements due to the averaging ability of the Lab-on-Disk readout while scanning the sensing films [9,10]. This experiment demonstrated that the film thickness information can be obtained from an optical disk drive-based absorbance measurement of a reference methylene blue reagent in the sensing film at 650 nm.…”
Section: Determination Of Sensing Films Thickness From Optical Disk Dmentioning
confidence: 83%
“…During initial feasibility studies with manually deposited films, it was shown that the Lab-on-Disk system produced similar quantitative performance compared to a conventional spectrometer [9]. Next, a laboratory-scale automated production of sensing films with 14 different colorimetric chemistries per disk was developed [10]. A jewel-case fluidic system has also been developed that delivered controlled water volumes to multiple sensing films on the disk within a defined time window, enabling controlled reaction time of sensing films with water, and removed water prior to quantification in an optical disk drive [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gold nanoparticles and precipitates 80,82,83 have been used for this purpose, and particle labels also have been used to catalyze autometallography to boost the contrast, 32,78,80,81,84,85 similar to silver staining on a Western blot. An alternative colorimetric approach uses calcium-sensitive film on the disk that changes color upon uptake of calcium 86,87 but with significantly lower sensitivity than the silver staining approach. Fluorescence detection 73,77,88,89 on digital CD/DVD platforms typically does not acquire the data on the digital channel.…”
Section: B Digital Biological Compact Disksmentioning
confidence: 99%
“…As typically employed, the optical pickup is an electronically steered and stabilized microscope extracting information from tracks 0.74 µm wide at a linear velocity of ~4 m/s [19]. Because of these capabilities, the DVD optical pickup has been used to develop systems for interferometry [20], DNA chip detection [21], profile measurement [22], motion detection [2325], biosensing and chemical analysis [2628] and for confocal compact scanning optical microscopes [29]. Significant research and development has gone into the design of the components and the optics in the DVD pickup to improve performance and longevity.…”
Section: Introductionmentioning
confidence: 99%